Understanding Multiple Behavioral Risk Factors for Cancer in Rural Women. Issue 6 (5th July 2016) - Noonan, Devon; Dardas, Latefa; Bice‐Wigington, Tiffany; Sloane, Richard; Benjamin, Rebecca; Choi, Seung Hee; Simmons, Leigh Ann
Abstract: Objectives: To examine the demographic and health‐related factors associated with risk behaviors that have been linked to cancer including smoking, high BMI, and low physical activity. Design and Sample: A secondary analysis was conducted using data from Rural Families Speak about Health, a multistate, epidemiologic study of rural American women and their families ( N = 444). Measures: Validated measures for various demographic and health‐related items including tobacco use, BMI, physical activity, and depression were used. Results: Of the total sample with complete data ( n = 399), the mean age was 32 years and the majority were White (64%), married (67%), had a high school education or higher (73%), and had an annual household income of less than 40, 000 (90%). Regarding cancer risk behaviors, 36% of the sample were smokers, 39% reported low levels of physical activity, and 45% had a calculated BMI over 30. Thirty‐five percent of participants reported engaging in two or more risk behaviors. There were significant differences in income, perceived health status, and depression depending on the number of risk behaviors reported. Conclusions: Understanding combinations of risk behaviors can assist nurses and other health professionals in tailoring multiple health behavior change interventions to prevent cancer among rural women.